2010
DOI: 10.1021/jf100433p
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Contaminants in Bee Pollen from Southeastern Brazil

Abstract: A set of experiments was carried out to validate a method for inorganic contaminants in honeybee-collected pollen, consisting of digestion of the samples in a closed microwave-assisted system and quantification of 10 inorganic contaminants by ICP OES. Forty-three samples of Brazilian bee pollen, collected in southeastern Brazil during one year, were analyzed. Determination of these analytes is important both as bioindicators of pollution and to verify the safety of consuming the pollen itself. The method had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 32 publications
9
55
0
Order By: Relevance
“…(2013) (0.005-0.137 mg/100 g) and were similar to the average content value observed by Morgano et al (2010) for Brazilian samples (0.012 mg/100 g). Samples 3, 4 and 5 failed to meet the standards for Cd and Pb levels in bee pollen (0.003 mg and 0.05 mg/100 g, respectively) proposed by Campos et al (2008).…”
Section: Mineral Contaminantssupporting
confidence: 65%
See 2 more Smart Citations
“…(2013) (0.005-0.137 mg/100 g) and were similar to the average content value observed by Morgano et al (2010) for Brazilian samples (0.012 mg/100 g). Samples 3, 4 and 5 failed to meet the standards for Cd and Pb levels in bee pollen (0.003 mg and 0.05 mg/100 g, respectively) proposed by Campos et al (2008).…”
Section: Mineral Contaminantssupporting
confidence: 65%
“…Barium (Ba) was present at the highest levels (0.393-1.593 mg/100 g), comprising about 52% of total mineral contaminants. Morgano et al (2010) found an average Ba content of 0.541 mg/100 g in 43 samples of bee-pollen from three Brazilian States (São Paulo, Minas Gerais and Espírito Santo). Ba compounds have many industrial applications and their toxicity depends on their solubility in water or in the gastric juice (Berman, 1980).…”
Section: Mineral Contaminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conti and Bortè [13] found less Cr in all bee pollen samples from areas of varied contamination. Morgano et al [20] observed varied Cr levels in samples from southeastern Brazil, depending on collection time. They found higher levels of Pb (0.147 mg kg -1 ) and Cd (0.033 mg kg -1 ) in bee loads.…”
Section: Resultsmentioning
confidence: 99%
“…Contamination with arsenic and even more with cadmium, has been reported in bee pollen from several countries (Europe, China, Brazil), and the present study is a new alert for pollen from rural fields. For arsenic high concentrations were found in Brazil [20,21], with values ranging 0.01 to 2.65 µg/g, China [6], with 5.24 µg/g, and in Serbia with 0.104 to 5.573 µg/g [22], and 1.090 to 9.640 µg/g [23]. For cadmium, high values were found in Poland with 0.48 to 0.66 µg/g [24], and even from 45.6 to 92.0 µg/g [25].…”
Section: Micro-macroelementsmentioning
confidence: 99%